Ultrasound-assisted fortification of yellow sweet potato (Ipomoea batatas) with iron and ascorbic acid - Purizaca-Santisteban, Kateryn; Ruiz-Flores, Luis Alberto; Sócola, Zury; Chaves, Eduardo Sidinei; Espinoza-Delgado, Milagros del Pilar (Frontiers in Sustainable Food Systems, 2023)
This study aimed to evaluate the effect of ultrasound on the incorporation of iron and ascorbic acid in sweet potato (Ipomoea batatas) and evaluate the parameters to obtain an enriched food. The incorporation was carried out using dehydrated sweet potato cubes submerged in 0.1% m/v ferrous sulfate and 1% m/v ascorbic acid solutions, treated at different times and sonication frequencies (37 and 80 kHz), at 100 watts of power and 30 ± 5 ºC. ANOVA and Tukey's test at a 5% significance level was applied to establish significant differences and the process was evaluated using a factorial design. The results revealed that the application of ultrasound influences the iron and ascorbic acid content, incorporating more iron and ascorbic acid compared to samples not treated with ultrasound. Similarly, longer times led to higher incorporation of iron and ascorbic acid content in sweet potatoes; the frequency was not statistically significant. The highest iron content was 105.91 ± 0.03 mg/100g and for ascorbic acid, it was 392.65 ± 4.84 mg AAE/100g. The defined ultrasonic process conditions produced an increase of 4928.99% and 610.65%, respectively, in iron and ascorbic acid content in sweet potato.